2015
DOI: 10.1103/physrevb.91.121405
|View full text |Cite
|
Sign up to set email alerts
|

Nonlocal electromagnetic response of graphene nanostructures

Abstract: Nonlocal electromagnetic effects of graphene arise from its naturally dispersive dielectric response. We present semianalytical solutions of nonlocal Maxwell's equations for graphene nanoribbon arrays with features around 100 nm, where we found prominent departures from its local response. Interestingly, the nonlocal corrections are stronger for light polarization parallel to the ribbons, which manifests as an additional broadening of the Drude peak. For the perpendicular polarization case, nonlocal effects le… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“…[53][54][55] For example, intrinsic optical phonons of graphene, scatterings from the edges as well as surface polar phonons in substrate like SiO 2 may lead to a significantly modified plasmon dispersion and damping, edge states may cause a red-shift and broadening of the plasmon resonance in doped graphene nanodisks with zigzag edges, and nonlocal response arised from spatial inhomogeneity will also affect plasmonic resonances in graphene nanostructures. A very recent study also reported the progress in achieving high confinement and low levels of plasmon damping by sandwiching graphene in an exceptionally clean environment with hexagonal boron nitride films.…”
mentioning
confidence: 99%
“…[53][54][55] For example, intrinsic optical phonons of graphene, scatterings from the edges as well as surface polar phonons in substrate like SiO 2 may lead to a significantly modified plasmon dispersion and damping, edge states may cause a red-shift and broadening of the plasmon resonance in doped graphene nanodisks with zigzag edges, and nonlocal response arised from spatial inhomogeneity will also affect plasmonic resonances in graphene nanostructures. A very recent study also reported the progress in achieving high confinement and low levels of plasmon damping by sandwiching graphene in an exceptionally clean environment with hexagonal boron nitride films.…”
mentioning
confidence: 99%
“…As shown in Fig. 9 and 10, it is noted that the both the real and imaginary parts of the impedance matrix shows a frequency shift and some amplitude variation while the shapes kept similar, which is due to that the nonlocal effects has directly influence on the propagating wave number including the phase constant [19]- [21], thus the relative electric length of the GNR is changed compared with the local model case, which directly results in the variations of the peaks and nulls of the impedance matrix.…”
Section: B a Graphene Nano-ribbon Power Dividermentioning
confidence: 89%
“…Since the solutions in DGTD method are allowed to be discontinuous at the interface of neighboring domains, the values with superscript * from (19) to (23) are named as numerical flux that are used for communication between adjacent domains in order to guarantee an unique solution.…”
Section: A Surface Impedance Boundary Condition In the Presence Of Smentioning
confidence: 99%
See 1 more Smart Citation
“…[12] Graphene also has been extensively investigated aiming toward potential applications in advanced photonics. [13][14][15][16][17] Graphene supports stronger bonding of surface plasmons, [18][19][20][21][22][23][24][25][26][27][28][29] and the Dirac fermions provides large tunabilities in optical response via magnetic field, electrostatic field, and doping in ultra-wide bands. [30][31][32][33] Compared to the conventional plasmonic materials-noble metals, the plasmonic resonance of graphene resides in the technically important bands: terahertz and infrared frequencies.…”
Section: Introductionmentioning
confidence: 99%